Proteomic Analysis of Atrial Appendages Revealed the Pathophysiological Changes of Atrial Fibrillation - Liu, Ban; Li, Xiang; Zhao, Cuimei; Wang, Yuliang; Lv, Mengwei; Shi, Xin; Han, Chunyan; Pandey, Pratik; Qian, Chunhua; Guo, Changfa; Zhang, Yangyang (Frontiers in Physiology, 2020)
Atrial fibrillation (AF), known as the most common arrhythmia in the developed world, affects 1.5-2.0% of the population. Numerous basic studies have been carried out to identify the roles of electric, structural and contractile remodeling in the pathophysiological changes of AF, but more explorations are required to further understand the mechanisms of AF development. Proteomics enables researchers to identify protein alterations responsible for the pathological developing progresses of diseases. Compared to the genome, the proteome is closely related to the disease phenotype and can better manifest the progression of diseases. In this study, AF patients proteomically analyzed to identify possible mechanisms. Totally 20 patients undergoing cardiac surgery (10 with paroxysmal AF and 10 with persistent AF) and 10 healthy subjects were recruited. The differentially expressed proteins identified here included AKR1A1, LYZ, H2AFY, DDAH1, FGA,FGB, LAMB1, LAMC1, MYL2, MYBPC3, MYL5, MYH10, HNRNPU, DKK3, COPS7A, YWHAQ, and PAICS. These proteins were mainly involved in the development of structural remodeling. The differently expressed proteins may provide a new perspective for the pathological process of AF, and may enable useful targets for drug interference. Nevertheless, more research in terms of multi-omics is required to investigate possible implicated molecular pathways of AF development.